Sinergisitas Lembaga Perkreditan Desa (LPD) Dalam Membangun Perekonomian Masyarakat - I Gusti Ngurah Putra Suryanata (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThis study aims to explain about 1) the synergy of Village Credit Union (Lembaga perkreditan Desa – LPD) in Kedonganan Village in developing the social welfare and 2) to maintain the competitive advantage of LPD in Kedonganan Village in developing the social welfare. The background theory that is used in this study are Synergy Theory and Social Capital Theory. This study used qualitative method with case study approach. The data in this study is collected by in-depth interview and unstructured interview. The result of this study shows that LPD in Kedonganan Village have done a synergy with the Kedonganan’s village boards and the society to build social welfare. When doing the synergy, they use Social Capital approach, which are building a networking with micro and macro financial institutions around Kedonganan Village with Dharma (Kindness) and Catur Purusa Artha (Trust) as the basic principals. The administrator of the LPD also creating trust in society by using Tri Hita Karana as the concept. The rule that is used in maintaining LPD also referring to common law that is called as awig-awig or perarem which has become a mutual agreement among Kedonganan Village society. To maintain the competitive advantage of LPD in developing social welfare, the manager or administrator of LPD should care about internal and external factors.